2021
DOI: 10.1088/1361-6595/ac278d
|View full text |Cite
|
Sign up to set email alerts
|

Zero-dimensional and pseudo-one-dimensional models of atmospheric-pressure plasma jets in binary and ternary mixtures of oxygen and nitrogen with helium background

Abstract: A zero-dimensional (volume-averaged) and a pseudo-one-dimensional plug-flow (spatially resolved) model are developed to investigate atmospheric-pressure plasma jets operated with He, He/O2, He/N2 and He/N2/O2 mixtures. The models are coupled with the Boltzmann equation under the two-term approximation to self-consistently calculate the electron energy distribution function. An agreement is obtained between the zero-dimensional model calculations and the spatially averaged values of the plug-flow simulation res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 165 publications
0
16
0
Order By: Relevance
“…N 2 + and NO could be found in the OES. Furthermore, N 2 + particles could be finally converted to NO by a serious reaction with the O 2 and N 2 in the air ( He et al, 2021 ). Previous studies from us and other groups have also shown that APP treatment could lead to upregulation of intracellular and extracellular NO productions ( Yan et al, 2012 ; Preissing et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…N 2 + and NO could be found in the OES. Furthermore, N 2 + particles could be finally converted to NO by a serious reaction with the O 2 and N 2 in the air ( He et al, 2021 ). Previous studies from us and other groups have also shown that APP treatment could lead to upregulation of intracellular and extracellular NO productions ( Yan et al, 2012 ; Preissing et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the plasma power increases, the electron density in atmospheric pressure plasma jets also increases. 46,47 An enhanced electron density leads to an enhanced electron impact dissociation of water to OH which in turn leads to a higher H 2 O 2 production. The saturation at high plasma powers might be due to too high OH density in the plasma so that the destruction of H 2 O 2 by OH might play a more important role.…”
Section: H 2 O 2 Concentration In Plasma-treated Liquidmentioning
confidence: 99%
“…Simulations of jets in curved tubes and in tube arrays are performed in 2D Cartesian coordinates [132][133][134][135]. Simulations focussing on the chemical kinetics in plasma jets can employ zero-dimensional and 1D models [136][137][138][139]. In this review, we focus on the discharge dynamics in single plasma jets.…”
Section: The Specificities Of Modelling Helium Pulsed Plasma Jetsmentioning
confidence: 99%